Adjunctive naturopathic care for type 2 diabetes: patient-reported and clinical outcomes after one year - Bradley Ryan; Sherman Karen J; Catz Sheryl; Calabrese Carlo; Oberg Erica B; Jordan Luesa; Grothaus Lou; Cherkin Dan (BMC, 2012)
Abstract Background Several small, uncontrolled studies have found improvements in self-care behaviors and reductions in clinical risk in persons with type 2 diabetes who received care from licensed naturopathic physicians. To extend these findings and determine the feasibility and promise of a randomized clinical trial, we conducted a prospective study to measure the effects of adjunctive naturopathic care (ANC) in primary care patients with inadequately controlled type 2 diabetes. Methods Forty patients with type 2 diabetes were invited from a large integrated health care system to receive up to eight ANC visits for up to one year. Participants were required to have hemoglobin A1c (HbA1c) values between 7.5-9.5 % and at least one additional cardiovascular risk factor (i.e., hypertension, hyperlipidemia or overweight). Standardized instruments were administered by telephone to collect outcome data on self-care, self-efficacy, diabetes problem areas, perceived stress, motivation, and mood. Changes from baseline scores were calculated at 6- and 12-months after entry into the study. Six and 12-month changes in clinical risk factors (i.e., HbA1c, lipid and blood pressure) were calculated for the ANC cohort, and compared to changes in a cohort of 329 eligible, non-participating patients constructed using electronic medical records data. Between-cohort comparisons were adjusted for age, gender, baseline HbA1c, and diabetes medications. Six months was pre-specified as the primary endpoint for outcome assessment. Results Participants made 3.9 ANC visits on average during the year, 78 % of which occurred within six months of entry into the study. At 6-months, significant improvements were found in most patient-reported measures, including glucose testing (P = 0.001), diet (P = 0.001), physical activity (P = 0.02), mood (P = 0.001), self-efficacy (P = 0.0001) and motivation to change lifestyle (P = 0.003). Improvements in glucose testing, mood, self-efficacy and motivation to change lifestyle persisted at 12-months (all P < 0.005). For clinical outcomes, mean HbA1c decreased by −0.90 % (P = 0.02) in the ANC cohort at 6-months, a −0.51 % mean difference compared to usual care (P = 0.07). Reductions at 12-months were not statistically significant (−0.34 % in the ANC cohort, P = 0.14; -0.37 % difference compared to the usual care cohort, P = 0.12). Conclusions Improvements were noted in self-monitoring of glucose, diet, self-efficacy, motivation and mood following initiation of ANC for patients with inadequately controlled type 2 diabetes. Study participants also experienced reductions in blood glucose that exceeded those for similar patients who did not receive ANC. Randomized clinical trials will be necessary to determine if ANC was responsible for these benefits.